Breastfeeding in Turkey: the demographic and socio-economic aspects and relationship with infant/child mortality - Tunçbilek, Ergül; Üner, Sunday; Ulusoy, Mahir (The Turkish Journal of Pediatrics, 1983)
The main findings of this study, which used data from the “1978 Turkish Fertility Survey”, are the following:The percentage of breastfed children of those born within the three years prior to the date of the survey was found to be 89.1. The percentage of breastfeeding of the penultimate child was 92.66, while the same figure was 93.32 for the last child, and mean durations of breastfeeding were 11.91, 16.89 and 15.87 months respectively.It was seen that unwanted children were breastfed longer than wanted children, because of belief in the contraceptive effect of breastfeeding.According to the results of the study, the less the mother’s education, the longer the breastfeeding period. The duration of breastfeeding gradually declined from Eastern Anatolia to the west and from villages to the cities. A positive relation was found between the duration of breastfeeding and the mother’s age, and boys were breastfed longer than girls.A statistically significant relation between breastfeeding duration and infant mortality was found in the closed interval, but all other independent variables considered jointly provided an explanation for only 13.6% of the changes in breastfeeding, which suggests that many variables which we could not include in the scope of this survey may affect breastfeeding.
Keywords: breastfeeding; child mortality; contraceptive effect; contraceptive usage; demographic variables; infant mortality; sex of baby; socio-economic factors